Recovery Process for Critical Metals: Selective Adsorption of Nickel(II) from Cobalt(II) at Acidic Condition and Elevated Temperature - Friederike Kriese; Stephan Lassen; Bernd Niemeyer (Adsorption Science & Technology)
Effective and sustainable separation processes for critical metals, especially for the physicochemically similar elements nickel and cobalt in battery recycling, are of great interest in the future. Selective adsorption represents a highly potential process for this purpose. In this publication, a silica adsorbent functionalized with an amino-polycarboxylate derivate (HSU331) was investigated regarding the selective adsorption of Ni(II) in the presence of Co(II) in acidic solution (pH range at equilibrium 1.8–2.3) at elevated temperature. Comparable maximum equilibrium loadings (qmax) for Ni(II) and Co(II) of 0.59 μmol(Ni(II)) · μmol(Ligand)-1 (18.3 mg(Ni(II)) · g(Adsorbent)-1), and 0.52 μmol(Co(II)) · μmol(Ligand)-1 (16.0 mg(Co(II)) · g(Adsorbent)-1), respectively, were achieved at T = 50°C in single-component experiments. Under competitive conditions, the Ni(II) loading remained constant at 0.60 μmol(Ni(II)) · μmol(Ligand)-1 (18.4 mg(Ni(II)) · g(Adsorbent)-1), while the Co(II) loading drastically decreased to 0.09 μmol(Co(II)) · μmol(Ligand)-1 (2.7 mg(Co(II)) · g(Adsorbent)-1) in an equimolar dual-component system. Calculated stability constants of 3 · 103 and 0.7 · 103 L · mol-1, respectively, for the formed metal ion complexes of Ni(II) and Co(II) onto the adsorbent HSU331, clarify the clear selectivity of the adsorbent towards Ni(II) in the presence of Co(II) even at elevated temperature (T = 50°C).